2015
DOI: 10.12659/msm.894303
|View full text |Cite
|
Sign up to set email alerts
|

XPD Functions as a Tumor Suppressor and Dysregulates Autophagy in Cultured HepG2 Cells

Abstract: BackgroundRecent clinical studies have linked polymorphisms in the xeroderma pigmentosum group D (XPD) gene, a key repair gene involved in nucleotide excision repair, to increased risk of hepatocellular carcinoma (HCC). However, the cellular effects of XPD expression in cultured HCC cells remain largely uncharacterized. Therefore, the aim of this study was to characterize the in vitro cellular effects of XPD expression on the HCC cell line HepG2.Material/MethodsHepG2 cells were transfected as follows to create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…With specific respect to HCC, recent studies have tied XPD to increased HCC susceptibility [20, 21]. XPD expression serves as a tumor suppressor in HCC [22]. To better understand XPD’s role in HCC, we investigated the in vitro cellular effects of XPD expression in HCC cells through transfection of the XPD gene into the HCC cell line SMMC7721 and Hep3B.…”
Section: Discussionmentioning
confidence: 99%
“…With specific respect to HCC, recent studies have tied XPD to increased HCC susceptibility [20, 21]. XPD expression serves as a tumor suppressor in HCC [22]. To better understand XPD’s role in HCC, we investigated the in vitro cellular effects of XPD expression in HCC cells through transfection of the XPD gene into the HCC cell line SMMC7721 and Hep3B.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is characterized by the presence of a large number of autophagosomes in the cytoplasm, and various digestive enzymes in the lysosome digest and degrade the contents in the vacuoles to convert them into substances required by the body for energy ( 32 , 33 ). Several studies have confirmed that autophagy plays an important role in tumorigenesis and therapy ( 34 – 36 ). However, reports on the effect of autophagy induced by drugs in tumor cells are not consistent and suggest that autophagy can have synergistic or antagonistic effects with apoptosis ( 37 , 38 ).…”
Section: Introductionmentioning
confidence: 98%
“…XPD751 polymorphism has been shown to be associated with the occurrence and development of a wide range of malignancies, such as esophageal cancer, gastric cancer, and colorectal cancer (26)(27)(28). Previous studies have demonstrated that XPd expression serves as a tumor suppressor in Hcc (10,11,29). In a present study by the authors, it was found that the mRNA and protein expression levels of XPD in ESCC tissue samples were significantly lower than those in the adjacent normal esophageal tissue samples.…”
Section: Discussionmentioning
confidence: 40%